2010
DOI: 10.3390/md8010080
|View full text |Cite
|
Sign up to set email alerts
|

Geoditin A Induces Oxidative Stress and Apoptosis on Human Colon HT29 Cells

Abstract: Geoditin A, an isomalabaricane triterpene isolated from the marine sponge Geodia japonica, has been demonstrated to dissipate mitochondrial membrane potential, activate caspase 3, decrease cytoplasmic proliferating cell nuclear antigen (PCNA), and induce apoptosis of leukemia cells, but the underlying mechanism remains unclear [1]. In this study, we found fragmentation of Golgi structure, suppression of transferrin receptor expression, production of oxidants, and DNA fragmentation in human colon cancer HT29 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Biochemical data also concurs with this result: isomalabaricane triterpenes have been found in R. globostelletta and Geodia japonica [66], [67]. Rhabdastrella species from our study are distributed in three groups: 1) R. globostelletta and Rhabdastrella sp.…”
Section: Discussionsupporting
confidence: 91%
“…Biochemical data also concurs with this result: isomalabaricane triterpenes have been found in R. globostelletta and Geodia japonica [66], [67]. Rhabdastrella species from our study are distributed in three groups: 1) R. globostelletta and Rhabdastrella sp.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study has also demonstrated a potent cytotoxicity of geoditin A against human leukemia HL60 cells (IC 50 = 3 µg/mL) [15], but mild to human colon carcinoma HT29 cells (IC 50 = 20 μg/mL) [14]. The IC 50 for murine melanoma B16 cells in this study also falls in this range, with the value of ≈10 μg/mL (Figure 2a).…”
Section: Resultssupporting
confidence: 66%
“…Our previous studies have also demonstrated geoditin A being a potent inducer of oxidative stress and apoptosis in HT29 cells [14] and HL60 cells [15]. It is the objective in this study to investigate if this oxidative stress might interfere with tyrosinase activity and melanogenesis in murine B16 melanoma cells.…”
Section: Introductionmentioning
confidence: 93%
“…Morphological alterations observed in the EAT cells treated with G. edulis such as ruffling, blebbing, condensation of the plasma membrane, and the aggregation of nuclear chromatin were in concurrent with the initial hypothesis. Involvement of ROS production in colon HT29 cells death induced by natural products derived from marine source demonstrated by individual investigators [ 51 , 52 ] and the nuclear fragmentation investigated as proof of induced apoptosis in oral squamous cell carcinoma cells [ 53 ]. Current drugs commonly used in anticancer therapy induce apoptosis in target cells, and it involves both receptor-mediated and mitochondrial-mediated pathways.…”
Section: Discussionmentioning
confidence: 99%